Financial integration in the GCC stock markets: evidence from the early 2000s development phase - Simpson, John (Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2008)
The GCC markets are the most advanced in economic reforms in the Middle East and have proceeded solidly towards regional integration during the early 2000s. Some of the GCC markets (for example Bahrain and the UAE) had made solid progress in their expansion, reforms and openness. Over the period there is evidence of cointigration of the UAE market with the other GCC markets in prices. Causality analysis shows the UAE was the major influence over prices in the Saudi Arabian, Kuwait and Qatar markets. The UAE already presents a strong case to be the regional financial centre if development continues strongly.